Enhancing organisational innovation capability – A practice-oriented insight for pharmaceutical companies. (July 2022) - Robb, Anna; Rohrschneider, Marc; Booth, Alex; Carter, Peggy; Walker, Richard; Andrews, Georgina
Abstract: This practice-oriented Insight paper draws on the academic literature, and the authors' experience in the pharmaceutical industry, to identify opportunities to enhance pharmaceutical innovation within a context of changing economic models in healthcare, including increasing R&D and manufacturing costs, and an increasing need to operate holistically (developing both drugs and devices). Specifically, we propose six recommendations for pharmaceutical organisations seeking to innovate effectively in this changing landscape: (1) improve the attention paid to employees' non-technical skills, (2) use a simultaneously top-down and bottom-up approach to innovation that provides on-the-ground support whilst being supported by senior management, (3) empower employees to engage in innovation, (4) address the tendency towards generic rather than adaptive, personalised, change programmes for innovation capability enhancement, (5) focus on specific team enhancements to demonstrate localised change, rather than trying to change a whole organisation's innovation capability at once, and (6) use coaching to embed changes designed to enhance innovation capability.